'Linguistic authority' in state-society interaction: cultural politics of Tibetan education in China. Issue 3 (4th May 2021) - Lhagyal, Dak
ABSTRACT: Situated in the contemporary contexts of Tibetan language movement and development in the education field, this article draws attention to the interactional nature of state-society relations and dynamic language ideologies in Tibet. It focuses on the ideological process underlying the discursive sensemaking patterns in official remarks and Tibetan reactions in the aftermath of a high-profile state intervention to reform Tibetan education in one part of the Tibetan region of Amdo in China. Although Tibetan people's concerns over language education and appeals to 'Tibetanness' empower them in resisting the repressive policy interventions from local authorities, this resistance also deploys the same metanarrative of legitimation that is fostered in state propaganda. As a result, Tibetan people's appeal to 'pure' language ideology accommodates speakers as much as it sets boundaries in the Tibetan society in the process.